2005
DOI: 10.1111/j.1600-0684.2005.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Demodex spp. in the hair follicles of rhesus macaques (Macaca mulatta)

Abstract: The perineal or perineal and facial skin were evaluated on 53 rhesus macaques as part of a necropsy protocol. Microscopic evaluation of H & E stained skin sections revealed 19 animals positive for Demodex spp. Mites were seen within all portions of the hair follicles. Infestation varied from minimal to severe. Mites were found in macaques of all ages and in both sexes. Reaction to the mites ranged from no reaction, to minimal follicular epidermal hyperplasia to furunculosis. Immune status of the animal did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…D. ovis has caused localized nodular lesions on the face of sheep. Previous research also demonstrated the nodular lesions of demodicosis (Starost et al 2005). Skin biopsies collected from sheep and goats infested by Demodex revealed acanthotic and hyperkeratotic epidermis.…”
Section: Discussionmentioning
confidence: 85%
“…D. ovis has caused localized nodular lesions on the face of sheep. Previous research also demonstrated the nodular lesions of demodicosis (Starost et al 2005). Skin biopsies collected from sheep and goats infested by Demodex revealed acanthotic and hyperkeratotic epidermis.…”
Section: Discussionmentioning
confidence: 85%
“…More recently, Demodex spp. were reported in the hair follicles of immunocompetent and immunocompromised rhesus macaques 103 . In this study, mites were found in the perineal and facial skin of 19 of 53 rhesus monkeys at necropsy regardless of age, sex or immune status.…”
Section: Introductionmentioning
confidence: 46%
“…mites have been documented in many nondomestic mammalian species 3,4,6,8,10,11,14-18, 23,26,[30][31][32]34 and all of the major domesticated mammal species, 28 but only occasionally do these mites cause demodecosis. An undescribed demodectic mite in hyraxes has previously been documented.…”
Section: Discussionmentioning
confidence: 99%